Effect of skipping breakfast for 6 days on energy metabolism and diurnal rhythm of blood glucose in young healthy Japanese males. Issue 1 (16th May 2019) - Ogata, Hitomi; Kayaba, Momoko; Tanaka, Yoshiaki; Yajima, Katsuhiko; Iwayama, Kaito; Ando, Akira; Park, Insung; Kiyono, Ken; Omi, Naomi; Satoh, Makoto; Tokuyama, Kumpei
ABSTRACT: Background: Skipping breakfast has become a common trend that may lead to obesity and type 2 diabetes. Previous studies, which imposed a single incidence of breakfast skipping, did not observe any decrease in 24-h energy expenditure. Furthermore, the effects of breakfast skipping on diurnal blood glucose profiles over 24 h are contradictory. Objective: The aim of this study was to clarify the influence of 6 consecutive days of breakfast skipping and sedentary behavior on energy metabolism and glycemic control. Methods: Ten young men participated in 2 trials (with or without breakfast) that lasted for 6 consecutive days, and the 2 trials were conducted 1 wk apart with a repeated-measures design. During the meal intervention, each subject's blood glucose was measured using the continuous glucose monitoring system. If breakfast was skipped, subjects ate large meals at lunch and dinner such that the 24-h energy intake was identical to that of the 3-meal condition. At 2200 on the fifth day, the subjects entered a room-sized respiratory chamber, where they remained for 33 h, and were instructed to carry out sedentary behavior. Results: The glucose levels were similar between the 2 meal conditions during the first 5 d of meal intervention, but the blood glucose at 2300 was higher in the breakfast-skipping condition than in the 3-meal condition. Breakfast skipping elevated postprandial glycemic response after lunch on the first day of meal intervention. On the sixth day, there were no significant differences in 24-h energy expenditure and substrate oxidation. When subjects remained in a metabolic chamber, the level of physical activity significantly decreased, glycemic stability slightly deteriorated, and mean blood glucose over 24 h was higher in the breakfast-skipping trial than in the 3-meal trial. Conclusions: Sedentary lifestyle and repeated breakfast skipping caused abnormal glucose fluctuations, whereas 24-h energy metabolism remained unaffected. Clinical Trial Registry: This trial was registered at http://www.umin.ac.jp/english/ as UMIN000032346.